CARDIOMETABOLIC SYNDROME AS A PREDICTOR OF ARTERIAL HYPERTENSION CLINICAL COURSE - I. G. Belyaeva; E. R. Smakaeva; G. A. Gritsaenko; L. N. Mingazetdinova (Российский кардиологический журнал, 2011)
The features of endothelial function and metabolic factors, such as insulin resistance and dyslipidaemia, were studied in 67 patients with arterial hypertension (AH) and obesity. It has been shown previously that in AH patients with metabolic disturbances, decreased endothelium-dependent vasodilatation, increased microalbuminuria, and elevated von Willebrand factor levels could facilitate the development and progression of endothelial dysfunction. Metabolic factors, such as insulin resistance and high blood pressure, become the markers of endothelial dysfunction in AH patients.